A phylogeny of howler monkeys (Cebidae: Alouatta) based on mitochondrial, chromosomal and morphological data - Villalobos, Federico (2004)
The current taxonomic status of the species and subspecies belonging to the genus Alouatta is addressed by combined phylogenetic analysis using morphological, kariotipyc and molecular data (mitochondrial genes cytocrome oxidase II and cytochrome B). Our result demonstrated that Alouatta palliata is the most basal taxon for the genus in concordance with previous studies, as well as showing the validity of the taxon Alouatta sara as a species. Also our analysis shows that the sex chromosome has evolved from a XY/XX system to a X1X2Y1Y2/X1X1X2X2 system within the genus, as well as an increase in the size and complexity of the hioideal bone.